2013
DOI: 10.1016/j.vaccine.2013.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Serotype distribution of Streptococcus pneumoniae isolated from patients with invasive pneumococcal disease in Brazil before and after ten-pneumococcal conjugate vaccine implementation

Abstract: The ten-pneumococcal conjugate vaccine (PCV10) was introduced into the national immunization program for childhood vaccination schedules by the Brazilian Health Public Service in March 2010. The aim of this study was to compare Streptococcus pneumoniae serotype distribution, antibiotic resistance patterns, and potential coverage before (January 2006-June 2010) and after (July 2010-September 2012) PCV10 introduction. The incidence of invasive pneumococcal disease (IPD), patient demographics, and disease charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 22 publications
4
27
1
6
Order By: Relevance
“…In a South African clinical trial for a 9-valent conjugate vaccine, rates of penicillin-resistant IPD and trimethoprim-sulfamethoxazole-resistant IPD decreased by 67% and 56%, respectively (303). dos Santos et al also found that penicillin and ceftriaxone nonsusceptibility decreased after PCV10 introduction in Brazil, although no trend was found for clindamycin, chloramphenicol, erythromycin, rifampin, tetracycline, or levofloxacin (304). In Colombia, penicillin resistance among invasive isolates decreased after PCV7 introduction (41.1% versus 14.2%; P ϭ 0.02) (305).…”
Section: Pneumococcal Conjugate Vaccines and Antibiotic Resistancementioning
confidence: 99%
“…In a South African clinical trial for a 9-valent conjugate vaccine, rates of penicillin-resistant IPD and trimethoprim-sulfamethoxazole-resistant IPD decreased by 67% and 56%, respectively (303). dos Santos et al also found that penicillin and ceftriaxone nonsusceptibility decreased after PCV10 introduction in Brazil, although no trend was found for clindamycin, chloramphenicol, erythromycin, rifampin, tetracycline, or levofloxacin (304). In Colombia, penicillin resistance among invasive isolates decreased after PCV7 introduction (41.1% versus 14.2%; P ϭ 0.02) (305).…”
Section: Pneumococcal Conjugate Vaccines and Antibiotic Resistancementioning
confidence: 99%
“…Currently, there are reports of 91 serotypes1 , 2 associated with CAP and other diseases. However, CAP causes greater morbidity and its occurrence is estimated at 13.8 million new cases worldwide each year 3…”
Section: Introductionmentioning
confidence: 99%
“…En Latinoamérica, incluyendo este estudio y un estudio colombiano (realizado por grupos etarios) y otro brasileño, el serotipo 14 se encuentra entre los más frecuentes (18,24) . El serotipo 19A es frecuente en otras partes del mundo, como lo reportan estudios de China (135 adultos) y Dinamarca (464 adultos), pero no resultó predominante en nuestro estudio ni en los latinoamericanos en referencia (18,(24)(25)(26) .…”
Section: Discussionunclassified
“…El serotipo 19A es frecuente en otras partes del mundo, como lo reportan estudios de China (135 adultos) y Dinamarca (464 adultos), pero no resultó predominante en nuestro estudio ni en los latinoamericanos en referencia (18,(24)(25)(26) . Las diferencias podrían darse por cambios temporales en la distribución de los serotipos, o por aspectos geográficos.…”
Section: Discussionunclassified